Lay People as Cross-Examiners: A Linguistic Analysis of the Libel Case McDonald's Corporation v. Helen Steel and David Morris - Tkačuková, Tatiana (International Journal of Speech, Language and the Law, 2011)
Awarding Institution: Masaryk University, Brno, Czech RepublicDate of Award: June 2010The PhD. thesis offers a detailed survey of linguistic problems lay litigants-in-person experience when cross-examining in court. It is a single-case study and the material for the analysis is drawn from the libel case McDonald’s Corporation v. Helen Steel and David Morris (tried in the UK High Court between June 1994 and December 1996). The thesis contrasts cross-examination questions and strategies used by the pro se litigants (Steel and Morris) with those used by the professional counsel representing McDonald’s (R. Rampton QC). It also aims to explore whether in the course of the case the two litigants-in-person improved their cross-examination skills and learned from the counsel. The thesis combines the quantitative approach with a qualitative analysis of the data. The quantitative part of the analysis is based on the corpus linguistics approach. The qualitative part draws on the methodology of conversation analysis, discourse analysis and the pragmatic approach. The findings of the study show that the pro se litigants improve their cross-examination skills, but their development remains unstable.